(untitled) (Olhar de Professor, 2020)
This article presents an exploratory study about school infrastructure and analyzes its connections with the performance of students in the final years of elementary school in Brazil Exam 2017 (Prova Brasil 2017). For that, techniques of descriptive and inferential statistics were used. Results indicate that Brazilian Schools, especially in North and Northeast regions still have got infrastructure deficit and some public politics adopted had not reached the expected result. It highlights the significant contribution of factors such as the presence of computer labs and internet, sport court, facilities for people with special needs (PNE), periodic garbage gathering and auditorium for the good school performance in analyzed evaluation. It is expected from the results obtained can be useful to guide public politics and to pique the interest in discussion about the impact of the material conditions of school enviroment on the quality education.